Galanin-Like Peptide's Association with Insulin Resistance in PCOS Patients - Ghanim, Elaf Kamal; Khalaf , Salim Jasim (Journal of Neonatal Surgery, 2025)
Background: Women in the reproductive age range are susceptible to the common complex endocrine condition known as polycystic ovarian syndrome, or PCOS. It has been demonstrated that galanin-like peptide (GALP) is linked to ovulation regulation. Objectives: The purpose of this study was to evaluate women with polycystic ovarian syndrome (PCOS) for reduced blood levels of Galanin-like peptide (GALP) and serum insulin resistance. Patients and methods: In this study, 40 healthy women who were age-matched to the PCOS patients were selected as the control group, while 100 women with PCOS between the ages of 15 and 45 took part: A cross-sectional study was conducted at Kirkuk City's hospitals and outpatient clinics between September and December 2024.Patients with PCO are diagnosed using the Rotterdam criteria. Participants were recruited after completing informed consent and having all eligibility requirements confirmed. The body mass index is computed both prior to and following treatment. The insulin resistance homeostatic model evaluation is calculated using the formula below.: An ELISA kit was used to assess the ratio of fasting insulin to fasting glucose by 405 galanin-like peptide (GALP) in human serum using the Enzyme-Linked Immunosorbent Assay technique. An automatic biochemical analyzer was used to assess the levels of triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and total cholesterol (TC). SPSS for Windows 7 was utilized for data analysis. Results: This group's serum levels of human GALP (galanin-like peptide) were considerably (p>0.01) lower than those of the control group. Serum levels of LDL and total cholesterol in PCOS patients were significantly higher than those in the control group (p>0.01). The serum levels of HDL, VLDL, and triglycerides are non-significant (p-value >0.05). Furthermore, compared to the control group, there was a substantial (p>0.01) rise in serum glucose and HOM-IR levels in PCOS patients. Conclusion: Women with PCOS had lower serum levels of human GALP (galanin-like peptide) than the control group.